Long-Term, Seasonal and Short-Term Fluctuations in the Water Level of the Southern Baltic Sea - Wolski, Tomasz; Wiśniewski, Bernard (Quaestiones Geographicae, 2014)
Aim of this work are analyses of oscillations sea levels in the Southern Baltic on a scale of short-term changes, seasonal and long-term (age). The study was based on observational data in different periods time for tide gauges station of the Polish coast. On the example of some storm situations presents the part of the baric wave and the wind in the formation of extreme sea levels. The primary cause of the annual variability of sea levels was the characteristics of the annual and semi-annual oscillations (the annual and semi-annual solar tide). In the work also determined the rate of long-term sea-level rise for the Polish coast.